Strategi Komunikasi Pemasaran Cooler City Rungkut Madya Dalam Meningkatkan Penjualan - Felisitas Cornelia Adelina; Riesta Ayu Oktarina; E. Rizky Wulandari (DIGICOM : Jurnal Komunikasi dan Media, 2025)
This research focuses on the phenomenon of a business entity operating in the ice cream & beverage sector called Cooler City Rungkut Madya. The background to this research is because the ice cream & beverage business in the last few years has been very fast and there are many enthusiasts and many brands have emerged in this business. In this research, researchers see how Cooler City Rungkut Madya faces challenges in maintaining and increasing sales. This research uses qualitative methods with descriptive research type. The results of this research are that Cooler City Rungkut Madya has implemented 4 marketing mix strategy indicators but has not maximized marketing online or through social media.